Evidence based communication for health promotion: Indian lessons of last decade - K Suresh (Wolters Kluwer Medknow Publications, 2011)
Good health promotion programs which help achieve public health goals are derived from using a mix of epidemiological and social and behavioral science research information. Social data informed by behavioral theories provides a lens of understanding how recommended behaviors are adopted by different individuals within the population over a period of time. In addition to social and epidemiological data, evidence based and scientifically planned and monitored strategic communication interventions have to be linked to available service components of the program. Communication is increasingly understood as an enabler of individual and social level change to achieve established developmental goals including health. Democratization movements and the advent of the internet have changed the environment around any program communication from top-down, expert-to-consumer (vertical) communication towards non-hierarchical, dialogue-based (horizontal) communication, through which the public increasingly questions recommendations of experts and public institutions on the basis of their own, often web based, research. The amount of information available has increased greatly, including scientifically valid data and evidence-based recommendations alongside poor quality data, personal opinions, and misinformation. Evidence-based approaches include engagement with and listening to stakeholders, and being transparent about decision making, and honest and open about uncertainty and risks. Decision and policy makers cannot assume what the public wants without undertaking social science and decision science research. The Global Polio Eradication Initiative and Integrated Disease Surveillance Projects (IDSP) in India haves shown that monitoring of public concerns needs to be continuous and responsive, and hand in hand with the monitoring of technical strategies and appropriate Information Technology support for, not only data transmission but also for videoconferencing and community involvement through toll free 24×7 call service with universal access. This article elucidates the vital role of Health Promotion, a research based communication process, in achieving developmental, particularly health goals. It underscores that communication is as much a science as an art, as much process as it is about outcomes. It advocates for increased linkages between epidemiological research and social science research in planning effective health promotion interventions with quality service delivery.